Water photovoltaic low-smoke halogen-free polyolefin composition as well as preparation method and application thereof

By adjusting the vinyl acetate content in the polyolefin resin and adding amphiphilic surfactant and combining with coupling agent, the problem of poor water breakdown performance of photovoltaic cable materials on water is solved, and high performance in long-term humid environments is achieved application.

CN119286115AActive Publication Date: 2025-01-10KINGFA SCI & TECH CO LTD

Patent Information

Application Number
CN202411536402.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-10
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

The existing water photovoltaic cable materials have poor water breakdown resistance in long-term humid environments and cannot meet the requirements of low smoke and halogen-free, which limits their application.

Method used

Polyolefin resin is used as the matrix to adjust the content of vinyl acetate and add amphiphilic surfactant, combine the coupling agent to improve the hydrophobic properties of the material and enhance the water breakdown resistance.

Benefits of technology

It significantly improves the water breakdown resistance of water photovoltaic cable materials, meets the needs of long-term humid environments, and ensures cable safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses an overwater photovoltaic low-smoke halogen-free polyolefin composition as well as a preparation method and application thereof. The polyolefin composition comprises the following components in parts by weight: 15-90 parts of polyolefin resin; 3 to 10 parts of polyolefin grafted maleic anhydride; 50 to 100 parts of a halogen-free flame retardant; 0.3 to 2 parts of a coupling agent; 0.3 to 1 part of an amphiphilic surfactant; 0.5 to 2 parts of a crosslinking auxiliary agent; wherein the content of vinyl acetate in the polyolefin resin is 14 wt%-26 wt%; the hydroxyl value of the amphiphilic surface active agent is 25 to 60 mgKOH / g. According to the invention, the polyolefin resin is selected as matrix resin, the content of vinyl acetate in the polyolefin resin is adjusted, the amphiphilic surfactant with a specific hydroxyl value is added, and the coupling agent is combined, so that the prepared polyolefin composition has better water breakdown resistance, and is particularly suitable for a water photovoltaic cable sheath material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cable materials, and specifically relates to a low-smoke halogen-free polyolefin composition for water photovoltaics, and a preparation method and application thereof. Background Art

[0002] As the development speed of photovoltaic power generation increases, the application mode of photovoltaic power generation shows a multi-field and diversified development trend. At present, large-scale land-based photovoltaic power generation projects are gradually becoming saturated, and there are a large number of places where floating photovoltaics can be installed in vast lakes, rivers and oceans.

[0003] However, water photovoltaics need to be immersed in water for a long time or in a humid environment for a long time, and the application environment is harsh; according to the standard requirements of photovoltaic cables, they need to meet the requirements of low smoke and halogen-free, so the flame retardant is mainly aluminum hydroxide or magnesium hydroxide, but it is very easy to absorb water and moisture, resulting in poor water breakdown resistance, which limits its application. Therefore, the present invention provides a low-smoke and halogen-free polyolefin composition for water photovoltaics, which has good water breakdown resistance, can meet the needs of long-term use in a humid environment, and ensure the safety of the cable. Summary of the invention

[0004] The purpose of the present invention is to overcome the defects or shortcomings of the low-smoke halogen-free polyolefin materials in the prior art, that is, the poor water breakdown resistance, and to provide a low-smoke halogen-free polyolefin composition for water photovoltaics.

[0005] Another object of the present invention is to provide a method for preparing the low-smoke halogen-free polyolefin composition for water photovoltaics.

[0006] Another object of the present invention is to provide an application of the low-smoke halogen-free polyolefin composition for water photovoltaics.

[0007] To achieve the above object, the present invention adopts the following technical solutions:

[0008] A low-smoke halogen-free polyolefin composition for water photovoltaics, comprising the following components calculated in parts by weight:

[0009]

[0010] Wherein, the content of vinyl acetate in the polyolefin resin is 14wt% to 26wt%; and the hydroxyl value of the amphiphilic surfactant is 25 to 60 mgKOH / g.

[0011] In the present invention, polyolefin resin is selected as the base resin, and the content of vinyl acetate in the base resin is adjusted to 14wt%-26wt% to ensure the surface polarity of the material. An amphiphilic surfactant is added and its hydroxyl value is adjusted to make the polar group close to the resin layer and the non-polar segment close to the outside, thereby reducing the surface free energy of the material. A coupling agent is used to improve the compatibility of the halogen-free flame retardant and the polyolefin resin, so that the interface is more solid and can resist the infiltration of water molecules, so that the material exhibits better hydrophobicity and thus has better water breakdown resistance.

[0012] It should be noted that, in the low-smoke halogen-free polyolefin composition for water photovoltaics described in the present invention, the content of the polyolefin resin in the base resin is preferably not less than 50wt%.

[0013] It should be noted that the vinyl acetate content in the polyolefin resin described in the present invention is 14wt% to 26wt%, for example but not limited to 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, 25wt% or 26wt%, etc., as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the specific point values ​​included in the range are no longer exhaustively listed in the present invention.

[0014] Furthermore, the vinyl acetate content in the polyolefin resin is 15-25wt%.

[0015] Furthermore, the vinyl acetate content in the polyolefin resin is 18-22 wt %. Within this range, it is easier to attract amphiphilic surfactants, so that the non-polar end is closer to the outside, and thus the water breakdown resistance of the polyolefin composition is better.

[0016] Specifically, the content of vinyl acetate in the polyolefin resin=(weight parts of ethylene-vinyl acetate×vinyl acetate content) / total weight parts of the polyolefin resin.

[0017] Specifically, the content of vinyl acetate in the ethylene-vinyl acetate is determined by infrared spectroscopy according to GB / T 30925-2014.

[0018] It should be noted that the hydroxyl value of the amphiphilic surfactant described in the present invention is 25 to 60 mgKOH / g, for example but not limited to 25 mgKOH / g, 30 mgKOH / g, 35 mgKOH / g, 40 mgKOH / g, 45 mgKOH / g, 50 mgKOH / g, 55 mgKOH / g or 60 mgKOH / g, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the specific point values ​​included in the range are no longer exhaustively listed in the present invention.

[0019] Furthermore, the hydroxyl value of the amphiphilic surfactant is 30 to 55 mgKOH / g.

[0020] Furthermore, the hydroxyl value of the amphiphilic surfactant is 33-52 mgKOH / g. The polyolefin composition prepared within this range has better water breakdown resistance.

[0021] Specifically, the hydroxyl value is measured with reference to GB / T 7383-2020 Method A (phthalic anhydride method).

[0022] Furthermore, the amphiphilic surfactant includes one or more of ethoxyamide wax, polyoxyethylene ether or polyethylene glycol.

[0023] Furthermore, the amphiphilic surfactant is polyoxyethylene ether. The polyolefin composition prepared by using this type of amphiphilic surfactant has better water breakdown resistance.

[0024] It should be noted that the amphiphilic surfactant described in the present invention is 0.5 to 1 part, for example but not limited to 0.5 part, 0.55 part, 0.6 part, 0.65 part, 0.7 part, 0.75 part, 0.8 part, 0.85 part, 0.9 part, 0.95 part or 1 part, etc. can all achieve the present invention.

[0025] It should be noted that the polyolefin resin described in the present invention can be selected by those skilled in the art from commonly used polyolefin resins as the base resin according to the prior art. For example, but not limited to, the polyolefin resin includes 0-25 parts of polyethylene, 15-40 parts of ethylene-vinyl acetate, and 0-25 parts of POE. In this dosage, it is particularly suitable for low-smoke halogen-free flame-retardant photovoltaic cable materials.

[0026] Furthermore, the polyolefin resin has a melt flow rate of 0.5 to 8 g / 10 min at 190° C. and a load of 2.16 kg.

[0027] Specifically, the test standard of the melt flow rate is GB / T 3682-2000.

[0028] Furthermore, the coupling agent includes a silane coupling agent and / or a titanate coupling agent.

[0029] Specifically, the silane coupling agent includes one or more of aminosilane, epoxysilane, and methacryloxysilane.

[0030] The titanate coupling agent includes pyrophosphate titanate and / or di(dioctyl phosphate)titanate glycol (ol) ester.

[0031] Furthermore, the cross-linking aid is one or more of triallyl isocyanurate, trimethylolpropane triacrylate, and trimethylolpropane trimethacrylate.

[0032] Furthermore, the halogen-free flame retardant is a hydroxide flame retardant.

[0033] Furthermore, the hydroxide flame retardant is magnesium hydroxide and / or aluminum hydroxide.

[0034] Furthermore, the polyolefin grafted with maleic anhydride is POE grafted with maleic anhydride and / or PE grafted with maleic anhydride.

[0035] Specifically, the maleic anhydride grafting rate of the polyolefin grafted with maleic anhydride is 0.5 to 2 wt %.

[0036] Specifically, the test method for the maleic anhydride grafting rate is an acid-base titration method.

[0037] Furthermore, the low-smoke zero-halogen polyolefin composition for water photovoltaics also includes 0.5 to 2.5 parts of calcium silicate. Adding calcium silicate can further improve the water impact resistance of the prepared polyolefin composition.

[0038] Furthermore, the low-smoke halogen-free polyolefin composition for water photovoltaics also includes 0.1 to 5 parts of an auxiliary agent.

[0039] Specifically, the auxiliary agent includes, for example but not limited to, one or more of an antioxidant, a lubricant, a weathering agent or a toner.

[0040] In the present invention, commonly used antioxidants may be selected, such as but not limited to one or more of hindered phenol antioxidants, phosphite antioxidants or thioester antioxidants.

[0041] Specifically, the hindered phenol antioxidant is N, N'-hexamethylene bis (3,5-di-tert-butyl-4-hydroxyphenyl propionamide) (Irganox 1098), pentaerythritol tetrakis [β- (3,5-di-tert-butyl-4-hydroxyphenyl) propionate (Irganox 1010), 1,3,5-tris (4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl) -1,3,5-triazine-2,4,6- (1H,3H,5H) -trione (antioxidant 1790), 1,6-hexanediol bis [3- (3,5-di-tert-butyl-4-hydroxyphenyl) propionate] (Irganox 259), β- (4-hydroxy-3,5-di-tert-butylphenyl) propionate octadecyl (Irganox 1076) or 3,9-bis{2-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)acrylate]-1,1-dimethyl}-2,4,8,10-tetraoxaspirocycloundecane (ADK AO-80) or more thereof.

[0042] The phosphite antioxidant is one or more of tris(2,4-di-tert-butylphenyl)phosphite (antioxidant 168), bis(2,6-di-tert-butyl-4-tolyl) pentaerythritol phosphite (PEP-36) or 627A.

[0043] The thioester antioxidant is one or more of distearyl thiodipropionate, didodecyl thiodipropionate (antioxidant DLTDP), dilauryl thiodipropionate or pentaerythritol dodecapropylthioate.

[0044] The present invention can select commonly used lubricants, such as but not limited to one or more of vinyl bisstearamide, polysiloxane, calcium stearate, magnesium stearate, zinc stearate, silicone, PE wax, or PP wax.

[0045] In the present invention, commonly used weathering agents can be selected according to the prior art, such as but not limited to hindered amine light stabilizers and benzotriazole ultraviolet light absorbers.

[0046] Specifically, the hindered amine light stabilizer is 2,2,6,6-tetramethyl-4-piperidinyl stearate and / or bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate.

[0047] Furthermore, the low-smoke halogen-free polyolefin composition for water photovoltaics comprises the following components calculated in parts by weight:

[0048]

[0049] The present invention also protects a method for preparing the above-mentioned low-smoke halogen-free composition for water photovoltaics, comprising the following steps:

[0050] The components are mixed uniformly in proportion by an internal mixer, extruded into granules by an extruder, and cooled to obtain the granules.

[0051] Specifically, the temperature of the internal mixer is 140-160°C.

[0052] In some specific embodiments, the components are mixed evenly in proportion in an internal mixer, and then added into a twin-screw extruder through a feeding port, with a length-to-diameter ratio of 40:1, a rotation speed of 300-400 rpm, and a temperature of 100-140°C. Thereafter, the mixture is extruded through a single screw extruder at a temperature of 100-140°C, granulated on an air-cooled die surface, and cooled to obtain the product.

[0053] The present invention also protects the use of the above-mentioned low-smoke halogen-free polyolefin composition for water photovoltaics in the preparation of water photovoltaic cable sheath materials.

[0054] Compared with the prior art, the present invention has the following beneficial effects:

[0055] The present invention provides a low-smoke halogen-free polyolefin composition for water photovoltaics. By adopting a polyolefin resin as a base resin, adding an amphiphilic surfactant, and adjusting the vinyl acetate content in the base resin, a synergistic coupling agent can improve the hydrophobicity of the polyolefin composition, and the composition has good water breakdown resistance, and is particularly suitable for water photovoltaic sheath materials. DETAILED DESCRIPTION

[0056] The present invention is further described in detail below in conjunction with specific examples, which are only used to explain the present invention and are not used to limit the scope of the present invention. The test methods used in the following examples are conventional methods unless otherwise specified; the materials and reagents used are reagents and materials that can be obtained from commercial channels unless otherwise specified.

[0057] 1. Raw materials used in each embodiment and comparative example:

[0058] Polyolefin resin:

[0059] Polyethylene (PE): LLDPE 3812PA, purchased from ExxonMobil;

[0060] Ethylene-vinyl acetate copolymer (EVA):

[0061] EVA1: EVA 7350M, VA content 18wt%, purchased from Taiwan Plastics Industry Co., Ltd.;

[0062] EVA2: EVA V6110MC, VA content 28wt%, purchased from Yangzi Petrochemical-BASF Co., Ltd.;

[0063] EVA3: ELVAX 40L-03, VA content 40wt%, purchased from DuPont, USA;

[0064] POE: POE 58750, purchased from Dow Chemical;

[0065] Halogen-free flame retardant: aluminum hydroxide, AH-01DG, purchased from Luoyang Zhongchao New Materials Co., Ltd.;

[0066] Coupling agent: aminosilane, KH-550, purchased from Anhui Guibao Organic Silicon New Materials Co., Ltd.;

[0067] Amphiphilic surfactants:

[0068] Amphiphilic surfactant 1: polyoxyethylene ether, UNITHOX 750, hydroxyl value 33 mgKOH / g, purchased from NuceraSolutions;

[0069] Amphiphilic surfactant 2: polyoxyethylene ether, UNITHOX 550, hydroxyl value 41 mgKOH / g, purchased from NuceraSolutions;

[0070] Amphiphilic surfactant 3: polyoxyethylene ether, UNITHOX 720, hydroxyl value 52 mgKOH / g, purchased from NuceraSolutions;

[0071] Amphiphilic surfactant 4: polyoxyethylene ether, UNITHOX 450, hydroxyl value 55 mgKOH / g, purchased from NuceraSolutions;

[0072] Amphiphilic surfactant 5: polyethylene glycol, PEG-3350, hydroxyl value 34 mgKOH / g, purchased from Dow Chemical;

[0073] Amphiphilic surfactant 6: polyoxyethylene ether, UNITHOX 480, hydroxyl value 22 mgKOH / g, purchased from NuceraSolutions;

[0074] Amphiphilic surfactant 7: polyoxyethylene ether, UNITHOX 420, hydroxyl value 85 mgKOH / g, purchased from NuceraSolutions;

[0075] Amphiphilic surfactant 8: polyethylene glycol, PEG-8000, hydroxyl value of 13 mgKOH / g, purchased from Dow Chemical;

[0076] Calcium silicate: purchased from Inner Mongolia Datang International Renewable Resources Co., Ltd.;

[0077] Calcium carbonate: CC-800, purchased from Jiangxi Guangyuan Chemical;

[0078] Polyolefin grafted maleic anhydride: POE grafted maleic anhydride, N423, purchased from Ningbo Nengzhiguang New Materials;

[0079] Cross-linking aid: triallyl isocyanurate, commercially available;

[0080] Antioxidant: a compound of antioxidant 1790, antioxidant 168 and antioxidant DLTDP in a mass ratio of 3:1:2, all of which are commercially available; it should be noted that the same raw materials are used in the parallel experiments of the examples of the present invention and the comparative examples.

[0081] 2. The polyolefin compositions described in the examples and comparative examples were prepared according to the formulations in Tables 1 to 2 by the following method:

[0082] The components were mixed evenly in proportion at 150°C in an internal mixer, and added into a twin-screw extruder through a feeding port with a length-to-diameter ratio of 40:1, a rotation speed of 350 rpm, and a temperature of 120°C. Thereafter, the product was extruded through a single-screw extruder at a temperature of 120°C, granulated on an air-cooled die surface, and cooled to obtain the product.

[0083] 3. Performance Testing

[0084] The polyolefin compositions prepared in the examples and comparative examples were extruded at 4 mm 2 The cable is subjected to a withstand voltage test in accordance with standard 2PFG 2750 / 09.20, and the withstand voltage test is required to be ≥2016h to meet the requirements.

[0085] Examples 1 to 12 and Comparative Examples 1 to 6

[0086] Table 1 Amount (unit: weight parts) and performance of each component in the low-smoke halogen-free polyolefin composition for water photovoltaic in Examples 1 to 12

[0087]

[0088]

[0089]

[0090] Table 2 Amount (unit: weight parts) and properties of each component in the polyolefin composition in Comparative Examples 1 to 6

[0091] Comparative Example 1 2 3 4 5 6 PE 5 5 5 / 5 5 EVA1 / / / / / / EVA2 / / / / 15 / EVA3 20 20 20 30 / 20 POE 15 15 15 10 20 15 Polyolefin grafted with maleic anhydride 5 5 5 5 5 5 Halogen-free flame retardant 60 60 60 60 60 60 Coupling agent 0.5 0.5 0.5 0.5 0.5 / Amphiphilic surfactant 1 / / / 0.5 0.5 0.5 Amphiphilic surfactant 6 0.5 / / / / / Amphiphilic surfactant 7 / 0.5 / / / / Amphiphilic surfactant 8 / / 0.5 / / / Crosslinking aid 1 1 1 1 1 1 Antioxidants 1 1 1 1 1 1 VA content in polyolefin resin (wt%) 20 20 20 30 10.5 20 Breakdown time(h) 1853 1984 1766 1962 1976 1928

[0092] It can be seen from Table 1 that the low-smoke halogen-free polyolefin composition for water photovoltaics prepared by the present invention has good water breakdown resistance. Specifically, the water breakdown time is not less than 2016h, meeting the 2PFG 2750 / 09.20 standard; more preferably, the water breakdown time is not less than 2200h.

[0093] From the comparison between Comparative Examples 1 to 3 and Examples 2 and 5 to 8, it can be seen that if the hydroxyl value of the selected amphiphilic surfactant is too low or too high, the water resistance breakdown time will be greatly reduced; this may be because when the hydroxyl value is too low, the polar groups in the polyolefin resin cannot be close to the resin layer, and the non-polar segments are close to the outside, resulting in a decrease in the breakdown time; if the hydroxyl value is too high, there will be more hydroxyl groups exposed on the surface, which makes it easy for moisture to enter the polyolefin composition, resulting in a decrease in water resistance breakdown performance.

[0094] From the comparison between Comparative Examples 4 to 5 and Examples 1 to 4, it can be seen that if the VA content in the polyolefin resin is too high or too low, the water-breakdown resistance of the obtained polyolefin composition decreases and cannot meet the requirements. This may be because when the VA content is too low, the non-polar end of the attracted amphiphilic surfactant is small, resulting in the polar end of the amphiphilic surfactant being close to the outside, the hydrophilicity is increased, and water is easy to enter the interior of the polyolefin composition, resulting in a decrease in water-breakdown resistance; when the VA content is too high, the surface polarity of the polyolefin composition is strong, resulting in enhanced hydrophilicity, thereby decreasing the water-breakdown resistance.

[0095] It can be seen from Comparative Example 6 that if no coupling agent is added, even if an amphiphilic surfactant is added and the VA content in the polyolefin resin is adjusted, the water breakdown resistance of the obtained polyolefin composition still cannot meet the requirements.

[0096] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A low-smoke, halogen-free polyolefin composition for water photovoltaics, characterized in that: The composition comprises the following components calculated by weight: Wherein, the content of vinyl acetate in the polyolefin resin is 14wt% to 26wt%; and the hydroxyl value of the amphiphilic surfactant is 25 to 60 mgKOH / g.

2. The low-smoke halogen-free polyolefin composition for water photovoltaics according to claim 1, characterized in that: The hydroxyl value of the amphiphilic surfactant is 30 to 50 mgKOH / g.

3. The low-smoke halogen-free polyolefin composition for water photovoltaic use according to claim 1, characterized in that: The amphiphilic surfactant includes one or more of ethoxyamide wax, polyoxyethylene ether or polyethylene glycol.

4. The low-smoke halogen-free polyolefin composition for water photovoltaics according to claim 1, characterized in that: The polyolefin resin includes 0 to 25 parts of polyethylene, 15 to 40 parts of ethylene vinyl acetate, and 0 to 25 parts of POE.

5. The low-smoke halogen-free polyolefin composition for water photovoltaics according to claim 1, characterized in that: The coupling agent includes a silane coupling agent and / or a titanate coupling agent.

6. The low-smoke halogen-free polyolefin composition for water photovoltaics according to claim 1, characterized in that: The halogen-free flame retardant is a hydroxide flame retardant.

7. The low-smoke halogen-free polyolefin composition for water photovoltaics according to claim 1, characterized in that: The cross-linking auxiliary agent is one or more of triallyl isocyanurate, trimethylolpropane triacrylate and trimethylolpropane trimethacrylate.

8. The low-smoke halogen-free polyolefin composition for water photovoltaics according to claim 1, characterized in that: It also includes 0.1 to 5 parts of auxiliary agents.

9. A method for preparing the low-smoke halogen-free polyolefin composition for water photovoltaics according to any one of claims 1 to 8, characterized in that: The steps include: The components are mixed evenly in proportion by an internal mixer, extruded into granules by an extruder, and cooled to obtain the granules.

10. Use of the low-smoke halogen-free polyolefin composition for marine photovoltaics according to any one of claims 1 to 8 in the preparation of marine photovoltaic cable sheath materials.

Citation Information

Patent Citations

  • Cracking-resistant thermoplastic low-smoke halogen-free flame-retardant polyolefin cable material

    CN103030917A

  • Low-cost water-resistant low-smoke halogen-free flame-retardant polyolefin sheath material and preparation method thereof

    CN113845717A

  • Hot-water-resistant oil-resistant thermoplastic low-smoke halogen-free flame-retardant polyolefin cable material

    CN114213741A

  • Halogen-free high-flame-retardant polyolefin sheath material and preparation method thereof

    CN114316417A

  • Marine photovoltaic cable sheath material and preparation method thereof

    CN117777586A

Cited By

  • Polyolefin composition as well as preparation method and application thereof

    CN120944233A